2015
DOI: 10.4236/ajps.2015.67094
|View full text |Cite
|
Sign up to set email alerts
|

Foliar Application of Micronutrients Enhances Wheat Growth, Yield and Related Attributes

Abstract: Wheat is one of the most essential foods in the world. To increase its productivity, nutrient management is one of the most important factors. To assess the possible role of micronutrients in improving wheat yield, an experiment was conducted to evaluate the wheat performance by foliar application of micronutrients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 10 publications
(9 reference statements)
9
39
0
Order By: Relevance
“…Until now, the information about multi nutrient foliar application is rare (Rawashdeh and Florin, 2015). Combine application of Mn and Fe and Fe + Mn + Zn resulted in best yields in wheat (Zain et al, 2015). Similarly, combined multi nutrient foliar application of on Lycopersicum and Beta vulgaris shows the highest yields compared to individual nutrient (Gobarah et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…Until now, the information about multi nutrient foliar application is rare (Rawashdeh and Florin, 2015). Combine application of Mn and Fe and Fe + Mn + Zn resulted in best yields in wheat (Zain et al, 2015). Similarly, combined multi nutrient foliar application of on Lycopersicum and Beta vulgaris shows the highest yields compared to individual nutrient (Gobarah et al, 2014).…”
Section: Introductionmentioning
confidence: 91%
“…This perhaps due to the basic role of Fe in plant respiration, photosynthetic processes and chlorophyll formation, Fe addition cause improvement in grain yield components. Application of micro-elements prominently improve grains spike -1 , 1000 grains weight, tillers meters -2 , grain yield, biological yields and harvest index of the wheat (Zain et al, 2015).…”
Section: /8mentioning
confidence: 99%
“…After analyzing the methods of fertilization and applying 120 kg•ha -1 nitrogen with the addition of Azofoska multi-component fertilizer at the BBCH stage of 23-29 (fertilization treatment 6), a significantly higher grain yield was obtained compared to a dose of 80 kg•ha -1 nitrogen applied either in the form of urea to the soil (fertilization treatment 1), urea with Azofoska fertilizer (fertilization treatment 2) or urea with Ekolist Mikro Z fertilizer (fertilization treatment 4). The effects of cereal production, resulting from the supplementation of basic NPK fertilization with fertilizers containing a combination of macro-and micronutrients, are not uniform (Gomaa et al, 2015;Wojtkowiak et al, 2015;Zain et al, 2015). Wojtkowiak et al (2015) found no effect of the extra to-the-soil fertilization with Azofoska and foliar fertilization with Ekolist on the yield of spring triticale grains.…”
Section: Resultsmentioning
confidence: 99%